Gambaran Residu Paparan Formalin pada Sampel Plasma Darah Karyawan Instalasi Hemodialisis Rumah Sakit - Anik Eko Novitasari; Rezki Febianti (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Hemodialysis is one of the installations in the hospital that handles blood washing therapy, by removing excess waste or harmful compounds, through a semi-permeable membrane which is carried out to replace kidney function that is no longer functioning properly. Hemodialysis is given to patients with a diagnosis of acute renal failure, terminal renal failure and patients who have severe poisoning with certain drugs. The research design was carried out descriptively. The aim of this research was to determine whether there was formalin exposure to hemodialysis workers or nurses when reusing or cleaning hemodialysis equipment, using a qualitative test. In this research, the results were obtained from 15 blood plasma samples, namely 6 positive formalin blood samples, with Schiff, Tollens, KMnO4 and Fehling reagents. It is known from the table of analysis results of qualitative test of formalin exposure on hemodialysis workers in one of the East Java Hospitals. For further research, it is hoped that quantitative tests will be carried out in determining the level of formalin in the blood using the instrument.